Environmental Planning of Two Selected River Basins of Western Ghats based on Investigations on Land Use Planning and Land Capabilities - Binoy Cherian T (Department of soil science and agricultural chemistry, College of Agriculture, 1987)
Rapidly changing socio economic structure puts tremendous pressure on human society to find additional resources for its sustenance. Indiscriminate exploitation of the natural resource with scarce concern for the ecological balance has caused disturbances and sometimes total destruction of important portions of the biosphere with immediate or delayed effects being evidenced on a global scale. Land and soil are not resources that are infinite and cannot be exploited for ever. This fragile epidermis of the earths crust is severely affected due to drastic changes in vegetation cover resulting in destruction of soils and losses of nutrients and fertility. The quality and quantity of terrestrial biosphere depends on the soil and land. For studying the extent and state of an environmental impact a well defined natural unit has to be selected. Being a natural physical system where the land and water act as definite determinants of land use, and since it is a well defined natural unit, river basins were chosen as the units for study. The sub water sheds and micro water sheds are the accepted units for ecodevelopment planning. There is a need for detailed studies in natural and agroeco systems in different water sheds in relation to the physical features of the land and soil characteristics. Such studies are required to plan microlevel aspects of eco restoration, and eco development of water sheds especially in Kerala where environmental degradation has reached alarming proportions. The main objectives of the work is as follows: 1. A study of the sub water sheds of Bharathapuzha and Aralampuzha for relief, morphology, drainage, geology, vegetation, climate, soil and land use. 2. A land capability assessment of both the river basins based on details soil studies and traversing of the area. 3. To evolve a set of recommendations for management of the two river basins. The basic approach in the present study is to investigate individual components and bring out their relationship with present land use, that would help to maintain the ecological balance while sustaining human needs. For this two river basins Mangalam-Gayatripuzha and Aralam-Bavalipuzha were selected. The former highly influenced by man and the latter relatively less interfered were chosen for making a comparative study. Environmental components like relief, slope, morphology, drainage, geology, vegetation, climate and soil have been analysed by using standard methodology with respect to individual variables. On the basis of these studies land capability was assessed for each geomorphic unit and the present land use was also studied. Finally a set of recommendations were evolved for the judicious use of each geomorphic unit. With minimum degradation to it. From the study it was found that the Mangalam-Gayatripuzha basin has a mature landscape in comparison with Aralam-Bavalipuzha basin with more diverse geomorphic units. The soil is mainly alluvial in Mangalam-Gayatripuzha basin whereas it is lateritic in Aralam-Bavalipuzha basin. Soil fertility is moderate with no marked variation in both cases. High population density, smaller land holdings and low per capita income have put the land to great stress. Ecologically viable land use based on land capability has become subservient to subsistence land use. Food crops dominate the agricultural scenary in the Mangalam-Gayatripuzha basin whereas cash crops take more area in the Aralam-Bavalipuzha basin. Both the basins are suspectible to erosion and this has been aggravated by large scale deforestation and cultivation of tuber crops on the hill sides. On the basis of these findings it is recommend that deforestation should be completely stopped and afforestation programmes expedited in order to conserve the ecology of both basins. Soil conservation measures should be taken up on a war footing in the Aralam-Bavalipuzha basin with the entire cost borne by the government. Comprehensive programmes must be formulated to bring the catchment of the rivers under good perennial tree and fodder vegetation. Tapioca cultivation requiring greater tillage on slopes should be discouraged or prohibited. A detailed land capability assessment based on natural land use determinates should be worked out for the two basins since large section of the people in the hilly areas are poor with no alternative means of subsistence. Imaginative hill slope agricultural programmes that guarantee subsistence for these people should be evolved.